Experiences of Bachelor of Secondary Education (BSED) Science Major Students in Participating in Academic Club Activities - Shaina Grace Meñoza; Louise Albert Lantaca; Khem Macalowa; Daisy Catubig; Alfer Jann Tantog; Genesis Naparan (Journal of Elementary and Secondary School, 2025)
This study investigated academic club activities in which participants engaged, examined the benefits and challenges they faced, and developed their coping strategies.  Participation in academic clubs can enhance students’ personal and academic development, fostering skills such as developing self-confidence, increasing the sense of belongingness, and acquiring new knowledge. However, these benefits can be accompanied by challenges, including time conflicts, delayed commencement, and plenty of contributions. This study employed a qualitative Merriam model case study method to explain the experiences of BSED Science major students participating in academic club activities and the benefits, challenges, and coping strategies they use to deal with the challenges encountered in participating in academic club activities. The methodology used in the study included interviews with 15 club members and 2 participants from the club officers, with triangulation. Data collected from each interview were analyzed in different categories. The findings revealed that the participants can benefit club members and officers. These are the following benefits: developed self-confidence, increased sense of belongingness, and acquired new knowledge. BSED Science major students also encountered challenges such as time conflict, delayed commencement, and considerable contribution. With these challenges, club members and officers devised three strategies to deal with them. The following strategies are used: setting priorities, patiently waiting for the event to start, and settling all contributions during clearance signing. Club officers and members are flexible and adaptable in any circumstances they encounter during their academic club activities to avoid unnecessary banter and conflicts